Removable partial dentures retained by hybrid CAD/CAM cobalt-chrome double crowns: 1-year results from a prospective clinical study: CAD/CAM cobalt-chrome double crowns: 1-year results - Herpel, Christopher; Springer, Antonia; Pushkin, Galmunkh; Zimmermann, Lukas; Stober, Thomas; Rammelsberg, Peter; Schwindling, Franz Sebastian (Journal of dentistry, 2021)
Objectives - Computer-aided design and manufacturing (CAD/CAM) has been successfully used to replace conventional steps in the fabrication of double crowns, creating hybrid-workflows that might facilitate the wider application of these restorations in the future. However, in-vivo data are still lacking. - Methods - A prospective clinical trial was designed in which 20 patients (median age = 69 years; n women = 10) with 73 abutment teeth who needed a double-crown-retained removable partial denture (RPD) were consecutively recruited. While most of the work steps were done conventionally, gypsum models were digitized with a laboratory scanner to allow CAD/CAM fabrication of primary crowns and secondary structures. DentalDesigner software (3Shape) was used in combination with milling unit PrograMillPM7 and Co-Cr- blanks (Ivoclar-vivadent). Connectors were milled from wax, transferred to Co-Cr using lost-wax technique and bonded to the secondary crowns. Clinical follow-ups were scheduled 6 and 12 months after prosthesis insertion. Outcome parameters were complication-free survival of RPDs and abutment teeth after one year. - Results - After 12 months, complication-free survival was 74% and 91% for the RPDs and abutment teeth, respectively. Complications comprised decementations (n = 5), abutment tooth fractures (n = 2), fracture of denture teeth (n = 1), and loss of abutment teeth (n = 1). These complications were easily manageable, resulting in 1-year survival of 100% for CAD/CAM RPDs. - Conclusions - First data on short-term complication rates of CAD/CAM double-crown-retained RPDs appear promising. To gather further evidence, prospective clinical trials over a longer follow-up time and with larger patient groups are required. - Clinical Significance - Hybrid CAD/CAM double-crown retained RPDs showed a successful clinical application after one year of follow-up. Further research is needed to evaluate their performance in comparison to conventional manufacturing methods.